Pengaruh Ekstrak Wortel (Daucus carota L.) terhadap Waktu Kematian Cacing Ascaris suum, Gooze in Vitro - Seno, Aryo; Haryati, Sri; Sakiman, Bambang Sukilarso (Nexus Biomedika, 2013)
Background : Carrots contain quercetin that can be used as antihelmintik. Quercetin is a class of flavonoid glycosides. This study aimed to determine the effect of carrotâs extract (Daucus carota, L.) against the death time of Ascaris suum, Goeze in vitro. Methods :This study was a laboratory experimental research using post-test only controlled group design. Subjects were Ascaris suum, Goeze which were still in active movement. Sampling technique used in this study was convenience sampling. Subjects were arranged into 7 groups, each group consisted of 4 worms, replication was done 4 times. Pyrantel pamoate 5mg/ml and physiological saline were successively added to the test solution of positive control and negative control group, while carrotâs Extract (Daucus carota, Linn) of 70%, 75%, 80%, 85% and 90% were added to the test solution of treatment groups. Worms were soaked in 25 ml of test solution and incubated at 37ÂºC. Observations were done every hour until all the worms died. Data were analyzed using Pearson correlation and linear regression. Results : There was a significant correlation between the concentration variables and time of death of the worms variable (p value of Pearson correlation was 0.000 (<0.050). The higher concentration of the carrot extract was the shorter time of death of worms (Correlation coefficient of concentration variable and time of death of the worms variable was - 0.960). The linear regression equation was Y = 53.775 - 0.609X. Conclusion : The Carrotâs extract (Daucus carota, Linn) had effects on acceleratingÂ  the time of death of Ascaris suum, Gooze in vitro. Keywords : Daucus carota, Linn extract, Ascaris suum, GoezeÂ